Discussion on the Treatment Strategy for Stage ⅡA1 Cervical Cancer (FIGO 2018) - Chen, Xiaolin; Liang, Wentong; Duan, Hui; Wu, Minling; Zhan, Xuemei; Dai, Encheng; Lv, Qiubo; Xie, Qinghuang; Liu, Ruilei; Xu, Yan; Bin, Xiaonong; Lang, Jinghe; et al. (Frontiers in Oncology, 2022)
Abstract And Keywords Abstract Objective This study aimed to explore the best treatment strategy for International Federation of Gynecology and Obstetrics (FIGO) 2018 stage ⅡA1 cervical cancer patients by comparing the survival outcomes of two treatment methods: abdominal radical hysterectomy (ARH) with standard postoperative therapy and radio-chemotherapy (R-CT). Methods Patients with FIGO 2018 stage ⅡA1 cervical cancer who underwent ARH or received R-CT were screened from the clinical diagnosis and treatment for cervical cancer in China (Four C) database. The recurrence cases between the two groups were analyzed. The 5-year overall survival (OS) and disease-free survival (DFS) of patients diagnosed with stage ⅡA1 cervical cancer in 47 hospitals in mainland China between 2004 and 2018 were compared by using propensity score matching (PSM). Results In the total study population, The R-CT group had higher recurrence (22.8% for the R-CT group and 11.2% for the ARH group, P<0.001) rates compared to the ARH group.The 5-year OS and DFS of the ARH group (n=776) were significantly higher than those of the R-CT group (n=167294) (OS: 91.8% vs. 77.8%, P<0.001; DFS: 86.5%vs. 69.1%, P<0.001)(OS: 91.8% vs. 76.4%, P<0.001; DFS: 86.5%vs. 73.9%, P<0.001). R-CT was associated with worse 5-year OS (HR=3.055, 95% CI: 1.829-5.103, P<0.001) and DFS (HR=2.815, 95% CI: 1.875-4.227, P<0.001)Multivariate Cox analysis showed a higher risk of death or recurrence in the R-CT group than in the ARH group (HR=3.185, 95% CI: 2.106-4.800, P<0.001; HR=2.377, 95% CI: 1.699-3.325, P<0.001). After 1:2 PSM, the 5-year OS and DFS of the ARH group (n=284478) were significantly higher than those of the R-CT group (n=262155) (OS:88.8% vs. 81.7%, P<0.001; DFS:85.8% vs. 74.0%, P<0.001OS:92.5% vs. 78.7%, P<0.001; DFS:88.6% vs. 75.3%, P<0.001). R-CT was still associated with worse 5-year OS (HR=1.946, 95% CI: 1.055-3.589, P=0.033) and DFS (HR=2.275, 95% CI: 1.372-3.772, P=0.001).Multivariate Cox analysis showed a higher risk of death or recurrence in the R-CT group than in the ARH group (HR=2.998, 95% CI: 1.810-4.965, P<0.001; HR=2.540, 95% CI: 1.683-3.834, P<0.001). Conclusion Our study demonstrated that for stage FIGO 2018 stage ⅡA1 cervical cancer patients, ARH offers better oncological outcomes than R-CT.